Rancang Bangun Sistem Pembayaran Kursus Mandarin Dengan Metode Waterfall - Teddy Marcus Zakaria; Julianti Kasih; Natanael Halim; Michael Sebastian Gunadi (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
The need for a computer-based system for Chinese language course institutions that still carry out the payment administration process manually, by writing payment details on receipts and student payment cards. The manual system makes the payment process longer and less efficient and requires more time to make financial reports. The problem is how to make the payment process more manageable, practical, efficient, and well-controlled. The computer-based payment management information system will solve this problem. In addition, there are additional benefits, good data management of students, and more detailed financial statements than manually. This research is develop a course payment system for the controlled management of student finances. The purpose is to prevent financial abuse and financial reporting more efficiently and accurately. The software engineering method used is Waterfall with the SDLC (Software Development Life Cycle) development model which is able to build the system in stages. It is hoped that with this system new student registration, payment processes and financial reports will be better for this course institution.The MandarinPro Course Payment System has been tested and used by Feng Huang Mandarin Course Bali to support student registration, course payments and financial reports. This system can be applied to similar courses.